DINAMIKA TERBENTUKNYA TANAH TIMBUL AKIBAT PASANG SURUT DI MUARA SUNGAI CIWULAN - Fauzi, Aditia; Lestari, Indri; Hakiki, Nisa; Sutrisno, Tri; Swardana, Ardli (J SIG (Jurnal Sains Informasi Geografi), 2023)
Coastal areas are border areas between land and sea areas. One of the phenomena that occurs in coastal areas is abrasion and sedimentation. Sedimentation results in the formation of raised soil in areas near the estuary. This research aims to identify the formation of emergent soil through continuous observation of Google Earth satellite images. The research was conducted at the mouth of the Ciwulan River, Karangnunggal District, Tasikmalaya Regency, West Java. The research was carried out in April – June 2023. The method used in this research was a comparison of each satellite each year. Based on observations of satellite imagery from year to year, it is observed that the volume of water in the Ciwulan River has increased, causing the area of emerging land to start to decrease from year to year in 2019, 2020, and 2021. The decrease in emerging land is due to abrasion at the mouth of the river, so the emerging land has disappeared because it was submerged by the high volume of river water.